2003
DOI: 10.1074/jbc.m211649200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Serum- and Glucocorticoid-inducible Protein Kinase, Sgk, Is a Cell Survival Response to Multiple Types of Environmental Stress Stimuli in Mammary Epithelial Cells

Abstract: The effects of multiple stress stimuli on the cellular utilization of the serum-and glucocorticoid-inducible protein kinase (Sgk) were examined in NMuMg mammary epithelial cells exposed to hyperosmotic stress induced by the organic osmolyte sorbitol, heat shock, ultraviolet irradiation, oxidative stress induced by hydrogen peroxide, or to dexamethasone, a synthetic glucocorticoid that represents a general class of physiological stress hormones. Each of the stress stimuli induced Sgk protein expression with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
176
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(188 citation statements)
references
References 81 publications
11
176
1
Order By: Relevance
“…A previous report demonstrated that SGK-1, but not Akt, is induced by various environmental stress stimuli and then subsequently protects cell from apoptosis induced by environmental stress. 27 Similarly, in this study, we determined that SGK-1 but not other sgk isoforms or Akt was upregulated after androgen stimulation. Our data also demonstrated that SGK-1 is critical for androgen-mediated survival in prostate cancer cells because eliminating SGK-1 expression abrogated androgen-induced death protection.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…A previous report demonstrated that SGK-1, but not Akt, is induced by various environmental stress stimuli and then subsequently protects cell from apoptosis induced by environmental stress. 27 Similarly, in this study, we determined that SGK-1 but not other sgk isoforms or Akt was upregulated after androgen stimulation. Our data also demonstrated that SGK-1 is critical for androgen-mediated survival in prostate cancer cells because eliminating SGK-1 expression abrogated androgen-induced death protection.…”
Section: Discussionmentioning
confidence: 57%
“…These data suggest that SGK-1 elimination leads to apoptosis, which is supported by previous reports. [26][27][28][29] Next, we confirmed that SGK-1 siRNA could induce apoptosis in another prostate cancer cell line. LNCaP cells were tested using a clonogenic assay.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Members of this group include Tsc22d3 (GILZ, Stojadinovic et al, 2007;Ayroldi and Riccardi, 2009) Other genes may display an astrocyte-specific response to GCs. GR-dependent signaling relies on the cellular context (Leong et al, 2003;Yu et al, 2011), which may be associated with the recruitment of cell-type specific GR coactivators (Grenier et al, 2006). The specific function of the GR-dependent genes in astrocytes identified in this work is as yet unknown.…”
Section: Gc Action On the Astrocytic Transcriptomementioning
confidence: 88%